Spectral X‐ray computed micro tomography: 3‐dimensional chemical imaging. (7th October 2020) - Sittner, Jonathan; Godinho, Jose R. A.; Renno, Axel D.; Cnudde, Veerle; Boone, Marijn; De Schryver, Thomas; Van Loo, Denis; Merkulova, Margarita; Roine, Antti; Liipo, Jussi
Abstract: We present a new approach to 3‐dimensional chemical imaging based on X‐ray computed micro tomography (CT), which enables the analysis of the internal elemental chemistry. The method uses a conventional laboratory‐based CT scanner equipped with a semiconductor detector (CdTe). Based on the X‐ray absorption spectra, elements in a sample can be distinguished by their specific K‐edge energy. The capabilities and performance of this new approach are illustrated with different experiments, i.e. single pure element particle measurements, element differentiation in mixtures, and mineral differentiation in a natural rock sample. The results show that the method can distinguish elements with K‐edges in the range of 20 to 160 keV, this corresponds to an element range from Ag to U. Furthermore, the spectral information allows a distinction between materials, which show little variation in contrast in the reconstructed CT image.